Metabolic Syndrome in People Older than 40 Years Old from Primary Care - Agustín Paramio Rodríguez; Yanet Letrán Sarría; Roicell Lázaro Requesén Gálvez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: metabolic syndrome is a condition of increasing prevalence, it triples the risk of developing atherosclerotic cardiovascular disease, and it is associated with obesity and unhealthy lifestyles. Early diagnosis is essential at the first level of care. Objective: to determine the metabolic syndrome behavior in people over 40 years of age from the medical office # 10, belonging to the Mártires de Calabazar Teaching Polyclinic in the Boyeros municipality. Methods: a descriptive cross-sectional study was carried out. The universe was made up of 553 people, of whom 376 were interviewed in the period from May 2017 to May 2018. The criteria of the Adult Treatment Panel III for the diagnosis of metabolic syndrome were followed. The descriptive variables were expressed in percentages and the Chi square statistical method was used to compare the variables under study. Results: the results obtained showed 14.63 % of people with metabolic syndrome, predominating the age groups of 40 to 59 years old with 54.55 % and males with 54.55 %. The 89.09 % have blood pressure figures ≥130/85 mmHg. 100 % of the people were unaware of their illness. Conclusions: predominance was found in people with metabolic syndrome of the male sex and of the age groups of 40 to 59 years old. Diagnosis at the first level of care is poor. Global cardiovascular risk is associated with increasing age and male sex.